Laboratory automation in the microbiology laboratory: an ongoing journey, not a tale? - Zimmermann, Stefan (Journal of clinical microbiology, 2021)
Clinical chemistry laboratories implemented fully automated devices decades before microbiologists started their subtle approaches to follow. Meanwhile several papers have been published about reduced time to reports, faster workflows, and increased sensitivity as results of lab automation. While the journey of automating microbiology workflows step by step was fascinating and beneficial, monetary aspects were uncommon in most publications. In this issue of the Journal of Clinical Microbiology, K. Culbreath, H. Piwonka, J. Korver, and M. Noorbakhsh (J Clin Microbiol 59:e01969-20, https://doi.org/10.1128/JCM.01969-20) calculate the benefits of total lab automation in terms of cost savings and lab efficiency in a “tale of four laboratories.” The authors here provide facts and solid calculations about the benefits achieved in four different-sized labs after implementation of full laboratory automation.
Gesehen am 25.03.2021